The Application of Management's New Theories in Nursing Care - H Dargahi (Tehran University of Medical Sciences, 2005)
Background & Aim: This paper investigate the application of some management's new theories in nursing care in order to determine the similarities between management and nursing. The need of Health Services to be effectively managed was a prominent features of developed countries health policy in the 1980 s and early 1990. In the recent years, four management's new theories has identified: organizational excellence, total quality management, organizational culture and empowerment. Each of these new theories has key role in nursing care. This paper identifies similarities and convergence's between management profession with nursing care, using application of management's new theories. Conclusion: The comparison between nursing care and management's new theories has been provided the collaboration and cooperation between nurses and management professions to deliver health care services to patients effectively.